2006
DOI: 10.1677/joe.1.06636
|View full text |Cite
|
Sign up to set email alerts
|

Centrally administered neuropeptide W-30 activates magnocellular neurosecretory cells in the supraoptic and paraventricular nuclei with neurosecretion in rats

Abstract: We examined the effects of i.c.v. administration of neuropeptide W-30 (NPW30) on plasma arginine vasopressin (AVP) and plasma oxytocin (OXT) using RIA. The induction of c-fos mRNA, AVP heteronuclear (hn)RNA, and c-Fos protein (Fos) in the supraoptic nucleus (SON) and paraventricular nucleus (PVN) of rats were also investigated using in situ hybridization histochemistry for c-fos mRNA and AVP hnRNA, and immunohistochemistry for Fos. Both plasma AVP and OXT were significantly increased at 5 and 15 min after i.c.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Taylor et al (2005) demonstrated activation of the hypothalamicpituitary-adrenal axis because of NPW23 activity in the parvocellular PVN. Kawasaki et al (2006) reported that centrally administered NPW caused activation of magnocellular neurosecretory neurons in the SON and PVN as well as significant increases in plasma arginine-vasopressin and oxytocin levels. Administration of NPW is also believed to significantly increase Fos expression in PVN and SON cells (Niimi and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Taylor et al (2005) demonstrated activation of the hypothalamicpituitary-adrenal axis because of NPW23 activity in the parvocellular PVN. Kawasaki et al (2006) reported that centrally administered NPW caused activation of magnocellular neurosecretory neurons in the SON and PVN as well as significant increases in plasma arginine-vasopressin and oxytocin levels. Administration of NPW is also believed to significantly increase Fos expression in PVN and SON cells (Niimi and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There is an apparently contradictory study showing that both OT and VP plasma levels can be elevated by i.c.v. NPW (21); however, this can be reconciled if, in the study showing elevated OT and VP, the OT and VP neurones had low activity levels, such that NPW‐induced depolarisation (and therefore release) would be the observed response to its introduction into the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Noxious stimuli for example, or intracerebroventricular injection of certain neuromodulators can influence transcription (Kawasaki et al, 2006;Kurose et al, 2001;Nomura et al, 1999;Onaka et al, 2003), and the specific mechanism(s) by which either physiological stimuli or exogenous substances result in magnocellular VP transcription remains unknown. With regards to the stimulus used in the current study, it has been shown by several independent laboratories that transcription of VP increases in response to a hyperosmotic stimulus (see Supp Table 1).…”
Section: Discussionmentioning
confidence: 99%